2021
DOI: 10.1523/jneurosci.3040-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 Induces the Release of Opioid Peptides from M1 Macrophages in Pathological Pain

Abstract: Interleukin-4 (IL-4) is an anti-inflammatory cytokine, which can be protective in inflammatory and neurologic disorders, and can alleviate pain. Classically, IL-4 diminishes pain by blocking the production of proinflammatory cytokines. Here, we uncovered that IL-4 induces acute antinociception by IL-4 receptor a (IL-4Ra)-dependent release of opioid peptides from M1 macrophages at injured nerves. As a model of pathologic pain, we used a chronic constriction injury (CCI) of the sciatic nerve in male mice. A sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…5 ). Because we have previously shown that IL-4 induced the release of opioid peptides from macrophages 22 , we also attempted to examine the mRNA of IL-4, but did not detect it in immune cells from inflamed paws of either DCF- or vehicle-treated control animals (data not shown).
Figure 5 Expression of inflammatory mediator mRNAs in inflamed paw tissue.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). Because we have previously shown that IL-4 induced the release of opioid peptides from macrophages 22 , we also attempted to examine the mRNA of IL-4, but did not detect it in immune cells from inflamed paws of either DCF- or vehicle-treated control animals (data not shown).
Figure 5 Expression of inflammatory mediator mRNAs in inflamed paw tissue.
…”
Section: Resultsmentioning
confidence: 99%
“…Rib bones were used as anatomical landmarks to identify L4, L5 and L6 DRG, which were then extracted using curved watchmaker forceps. The three DRG were pooled in a screw cap 1.5 ml tube, deep frozen in liquid nitrogen and stored at − 80 °C until RNA extraction 21 , 22 .…”
Section: Methodsmentioning
confidence: 99%
“…IL-4 plays a protective role in neurological disorders and can be analgesic. Pain relief is achieved in two ways: 12 , 13 (i) by blocking the production of pro-inflammatory cytokines (eg, IL-1β, tumor necrosis factor, prostaglandin E2), (ii) by applying IL-4 to damaged nerves, which can achieve analgesic effects through IL-4Rα-mediated release of opioid peptides from M1 macrophages; IL-4 can also transfer macrophages from the M1 phenotype to the M2 phenotype, resulting in the production of opioid peptides in damaged nerves for pain relief. IL-13 is a pleiotropic cytokine that can be produced by a variety of cells and is particularly well known in the field of allergy and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PLC, PKC or cyclic AMP/PKA signals enhances the activity of transient receptor potential vanilloid 1 (TRPV1), TRPA1 or Ca v 3.2 channels, known as pro-nociceptive cation channels, contributing to pathological pain [66][67][68][69] (Figure 2B). On the other hand, M2 macrophages secrete IL-10, which in turn suppresses neuronal excitability and neuropathic pain (Figure 2B), and there is also evidence for anti-nociceptive roles of macrophage-derived opioid peptides [70,71].…”
Section: Key Mediators Involved In a Macrophage-nociceptor Crosstalk 41 Macrophage-derived Pro-nociceptive Mediatorsmentioning
confidence: 99%